Rancang Bangun Alat Pengukur Suhu Tubuh Pintarberbasis Internet Of Things - Arif Rahman Halim; Muhammad Saiful; Lalu Kertawijaya (Infotek: Jurnal Informatika dan Teknologi, 2022)
Measurement of body temperature can be the basis for determining a person's health. The increase in body temperature can also be a reference to find out whether a person is experiencing early symptoms of an infectious disease such as Covid 19 which is currently a pandemic or just a common fever. Body temperature measurements were initially carried out manually using a thermogun and the use of a thermogun requires a person to be in direct proximity. which will increase the risk of contracting the disease. this research makes a smart body temperature measuring device based on the internet of things, internet of things is a concept that aims to expand the benefits of continuously connected internet connectivity such as the ability to share data, remote control, and so on, so it is hoped that with the use of internet technology of things this smart body temperature measuring device can be controlled remotely which is not limited by distance and time as long as the system is connected to the internet network. The system uses an ultrasonic sensor to detect a person and the MLX-90614 sensor for non-contact body temperature measurement to detect body temperature, after which the data will be processed by nodemcu. The data is then displayed through the blynk application which is connected in real time and the data that has been processed by esp8266 is also displayed using an OLED LCD and besides that, the output is in the form of sound as a notification using DFPlayer mini Mp3.